Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1996
DOI: 10.1055/s-2007-979848
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphism of the Human Ca2+-Sensing Receptor Gene in Japanese Individuals: No Relation to Non-Insulin Dependent Diabetes Mellitus

Abstract: A missense mutation in the Ca(2+)-sensing receptor (CaSR) gene was previously identified in a Japanese family with familial hypocalciuric hypercalcemia. Five members of this family with the mutation in the CaSR gene also showed abnormal glucose tolerance, whereas family members homozygous for the wildtype CaSR gene were normal in this respect. The potential relation between mutations in the CaSR gene and the incidence of diabetes mellitus was therefore investigated in 27 non-insulin dependent diabetic and 40 n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
1

Year Published

2000
2000
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 10 publications
0
9
1
Order By: Relevance
“…However, we could not observe a significant association between mutations of CaSR gene and type 2 diabetes mellitus (26). So, we concluded that the mutations of CaSR gene may not be direct a determinant for the development of diabetes mellitus or IGT in this family.…”
Section: Discussioncontrasting
confidence: 63%
“…However, we could not observe a significant association between mutations of CaSR gene and type 2 diabetes mellitus (26). So, we concluded that the mutations of CaSR gene may not be direct a determinant for the development of diabetes mellitus or IGT in this family.…”
Section: Discussioncontrasting
confidence: 63%
“…Six polymorphisms were found in the CASR gene: one (105) and, when analyzed in a large group of normal and affected individuals, no correlation was found between this mutation and the incidence of parathyroid adenoma or diabetes (106). The A/T 826 mutation was initially found in 4 parathyroid adenomas (107).…”
Section: Polymorphismsmentioning
confidence: 99%
“…The first exon of CASR could not be translated to protein. There is a large body of evidence now defining genotypic variation and its relation to phenotype and ethnic distribution of CASR, and for the association of its polymorphisms with some diseases such as hypertension [11], cancer [12,13] and diabetes [14,15]; however, with respect to urinary stone disease directly related with calcium homeostasis, more work is required. The incidence of urolithiasis is relatively high in Iran [16,17].…”
Section: Introductionmentioning
confidence: 99%